2000
DOI: 10.1177/01939450022044421
|View full text |Cite
|
Sign up to set email alerts
|

Self-Disclosure of HPV Infection to Sexual Partners

Abstract: Disclosure decisions of persons with genital HPV infection were examined. The research questions focused on relationships among knowledge of transmission, beliefs about the obligation to disclose knowledge of HPV infection to sexual partners, factors that influence the disclosure decision, and evaluations of the decision. Participants were 92 persons diagnosed with HPV 6 months prior to data collection. Sixty-three women and 29 men whose average age was 23.1 years constituted the sample. A subset of 48 persons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
27
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 16 publications
6
27
1
Order By: Relevance
“…Considering what factors might be relevant to the disclosure decision, one study suggested that disclosure of warts was more likely in longer-term than casual relationships 9. This is consistent with research in genital herpes populations 10.…”
supporting
confidence: 55%
“…Considering what factors might be relevant to the disclosure decision, one study suggested that disclosure of warts was more likely in longer-term than casual relationships 9. This is consistent with research in genital herpes populations 10.…”
supporting
confidence: 55%
“…[14][15][16][17][18] For this reason, information on HPV can also be challenging for clinicians to convey to patients. [16][17][18][19][20][21][22][23][24][25][26][27] HPV educational materials should be a viable source of accurate and meaningful information for women and should complement clinician counseling to reinforce important HPV information and to assist women with medical decision making. The purpose of this study was to formally evaluate printed HPV educational materials by determining the readability, suitability, and HPV content of existing, printed HPV educational materials selected by the authors.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the disclosure of having an STI has focused primarily on how individuals disclose their STI (Lee & Craft, 2002;Swanson & Chenitz, 1993) and their reasons for disclosure or non-disclosure (Green et al, 2003;Keller, von Sadovszky, Pankratz, & Hermsen, 2000;Lee & Craft, 2002). To date, there has been limited systematic research on whether factors influencing disclosure or non-disclosure of one's STI status differ according to whether a partner is a casual partner or a regular partner.…”
mentioning
confidence: 99%